2020
DOI: 10.1108/ijshe-02-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy, sustainability and teacher training in a higher education institution

Abstract: Purpose Higher education institutions have a valuable dual role in disseminating the circular economy (CE) as a new sustainability paradigm. First, the university teaches students about this subject. Second, it prepares future teachers to incorporate sustainability into other educational levels. This paper aims to present the results of implementing a set of activities designed to improve the attitudes and actions of students to reduce their daily impact on campus and to be active agents for change to the CE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Our analysis also confirmed that education for CE is highly related to sustainability education [27]. We found different skills and competences related to sustainable development in general and, more specifically, to sustainable goals [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our analysis also confirmed that education for CE is highly related to sustainability education [27]. We found different skills and competences related to sustainable development in general and, more specifically, to sustainable goals [18].…”
Section: Discussionsupporting
confidence: 82%
“…The education system is a key strategic actor to create the right conditions for the socio-technical transition towards a CE because of its fundamental role to develop societies and workforces that are more sensitive to sustainability goals, as well as to help create business leaders and policymakers with appropriate skills, competences, and consciousness referring to the CE challenge [26]. In this regard, education for CE has emerged as a new field of study concerning the role of higher education in supporting the CE transition through teaching, research, and practice [27].…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Studies of CE activities in colleges and universities include benefit analysis of the introduction of recyclable materials and recycling systems on campus (Barros et al, 2020;Tan & Li, 2016), the design of sustainable resource management schemes (Salguero-Puerta et al, 2019;Wil-liams & Powell, 2019) and other applications of CE principles in campus development (Hopff et al, 2019;Mendoza et al, 2019). Among them, CE education in universities is expected and has been considered one of the most pivotal factors to realize the transition toward the CE model (Bugallo-Rodriguez & Vega-Marcote, 2020). CE specialty education and general education in universities have been a broad concern for researchers, involving the establishment of talent training mode (Cui et al, 2018;Weissbrodt et al, 2020), construction and evaluation of the CE curriculum system (Kirchherr & Piscicelli, 2019;Nunes et al, 2018;Rodriguez-Chueca et al, 2020), and CE education in specific fields (Kopnina, 2019;Rokicki et al, 2020).…”
Section: Transformative Learning Theory and University Ce Activitiesmentioning
confidence: 99%
“…Several organizations and funded international projects have developed educational materials about circular economy aimed at primary and secondary schools, including downloadable lesson plans, instruction movies and class activities (The Ellen MacArthur Foundation, 2017;The Finnish Innovation Fund Sitra, 2019;Joāo, 2020;Foundation for Environmental Education, 2021). Still, research about suitable approaches to introduce circular economy concepts in secondary education is largely lacking as in most of the case studies higher education is the focus like for example in Kopnina (2018) and Bugallo-Rodríguez and Vega-Marcote (2020). In this paper, we want to contribute to filling this gap.…”
Section: Introductionmentioning
confidence: 99%